d x d y = 1 − ln y y 2 − y 1
Given that the above differential equation has its solution passing through ( 1 , 1 ) . Find the corresponding value of x when y = e e 1 . Input your answer as ⌊ 1 0 0 0 x ⌋ .
You may use a calculator for the final step of your calculation.
Clarifications :
e ≈ 2 . 7 1 8 2 8 denotes the Euler's number .
⌊ ⋅ ⌋ denotes the floor function .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
d x d y d x x = 1 − ln y y 2 − y 1 = y 2 − y 1 1 − ln y d y = ∫ y 2 − y 1 1 − ln y d y = ∫ y 2 y y 1 ( 1 − ln y ) d y Integrate both sides
Note that
d y d y y 1 = d y d e y 1 ln y = e y 1 ln y ⋅ d y d ( y ln y ) = y y 1 ( − y 2 ln y + y 2 1 ) = y 2 y y 1 ( 1 − ln y ) By chain rule
Therefore, we have:
⟹ x ⟹ 1 ⟹ C ⟹ x = ∫ y 2 y y 1 ( 1 − ln y ) d y = y y 1 + C = 1 + C = 0 = y y 1 = ( e 1 / e ) e 1 / e 1 = 1 . 2 9 0 0 0 5 3 6 9 C is the constant of integration. It is given that when x = 1 , y = 1
⟹ ⌊ 1 0 0 0 x ⌋ = 1 2 9 0
And here I was thinking how to make that into y = − l n ( x + c ) W ( − l n ( x + c ) ) . How ignorant of me hahaha
y y 1 − 2 ( 1 − l n y ) d y = d x
y y 1 ( y 2 1 − l n y ) d y = d x
∫ y y 1 ( y 2 1 − l n y ) d y = ∫ d x
y y 1 = x + c where c is an integration constant
From x = 1 , y = 1 we found c = 0
So the function is x = y y 1
We substiute (y)^(1/y = p and the thing on Right hand side is its derivative ie dp
Now it becomes a child's play to integrate
This was easy,I mean apart from finding approx value of x in the end, everything was hassle free.
Problem Loading...
Note Loading...
Set Loading...
Note: I hope someone would be able to give a more in-depth solution than mine, as I just reverse engineered a particular function I want to play along with and came up with this problem. :) (I actually started with the solution, then created the differential equation from it. It turns out the solving the equation requires the knowledge of the Lambert W Function, which is somehow a "just learned the surface of it" concept to me at the moment.)
So, I guess I'll just show how I arrived at the said differential equation from the original function, which, by the way, is the power tower function.
y = x x x x x . . .
This function gives finite values of y over the interval ( e − e , e e 1 ] .
We can simplify this function to
y = x y
taking logarithms of both sides,
l n y = y l n x
and by implicit differentiation,
y y ′ = x y + ( l n x ) y ′
by separating y ′ ,
y ′ ( y 1 − l n x ) = x y
so we get
y ′ = x [ 1 − y l n x ] y 2
but we know that y l n x = l n y , and x = y y 1 , so the RHS becomes free of x.
That's how I just got
y ′ = 1 − l n y y 2 − y 1
Okay so I have just verified that indeed, the power tower is a solution of this differential equation. What's the significance of ( 1 , 1 ) then?
In the event a solution has been found by solving the differential equation, an arbitrary constant will appear. Substituting that point to the values of x and y will determine its value and thus determine the specific function are looking for.
So using the equation x = y y 1 , we can now substitute y = e e 1 .
x = ( e e 1 ) e e 1 1
x = ( e e 1 ) ( e − e 1 )
x = ( e e 1 ⋅ e − e 1 )
x = e e e − e 1
x = e e − ( e 1 + 1 )
x ≈ 1 . 2 9 0 0 0